2007
DOI: 10.1371/journal.pbio.0050038
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Control of the foxp3 Locus in Regulatory T Cells

Abstract: Compelling evidence suggests that the transcription factor Foxp3 acts as a master switch governing the development and function of CD4+ regulatory T cells (Tregs). However, whether transcriptional control of Foxp3 expression itself contributes to the development of a stable Treg lineage has thus far not been investigated. We here identified an evolutionarily conserved region within the foxp3 locus upstream of exon-1 possessing transcriptional activity. Bisulphite sequencing and chromatin immunoprecipitation re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
1,089
9
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 1,115 publications
(1,177 citation statements)
references
References 51 publications
52
1,089
9
9
Order By: Relevance
“…It is therefore possible that, depending on the cell subset and/ or the stage of T cell differentiation, FOXP3 expression can exert different functions and act as a negative or positive regulator. This is consistent with the fact that FOXP3 is a gene highly subjected to epigenetic modifications [22], which may contribute to diversifying its function.…”
Section: Foxp3 Expression In T Cellssupporting
confidence: 87%
“…It is therefore possible that, depending on the cell subset and/ or the stage of T cell differentiation, FOXP3 expression can exert different functions and act as a negative or positive regulator. This is consistent with the fact that FOXP3 is a gene highly subjected to epigenetic modifications [22], which may contribute to diversifying its function.…”
Section: Foxp3 Expression In T Cellssupporting
confidence: 87%
“…The modifiable mediators of this regulation include methylation,37, 38, 39, 40, 41, 42, 43, 44 acetylation45, 46, 47 and microRNA‐mediated control of transcript translation 28, 48, 49, 50, 51, 52, 53, 54, 55. The global regulation of FOXP3 is influenced by chromatin organises, including SATB1 acts both during development and in mature cells 48, 58.…”
Section: Foxp3 Epigenetic Regulationmentioning
confidence: 99%
“…We recently identified a highly conserved region within the murine as well as the human FOXP3 gene locus that is completely [17,18]. We therefore analyzed the DNA methylation status of CD127 À Treg directly after isolation from PBMC to explore whether they contain significant numbers of in vivo induced Treg.…”
Section: Epigenetic Changes In the Foxp3 Gene Locus Upon In Vitro Expmentioning
confidence: 99%
“…Lastly, the possibility had to be considered that natural Treg do not maintain FOXP3 expression indefinitely, but have the capacity to down-regulate FOXP3 and to convert to cells with variable phenotypic and functional characteristics under certain circumstances such as chronic stimulation. Here, we aimed to clarify these issues with the help of two recent advances in the field: First, we recently described that natural Treg differ from other T-cell populations in their DNA methylation status of a defined region within the FOXP3 locus termed Treg-specific demethylation region (TSDR): Demethylation of this region is exclusively observed in natural Treg, but neither in activated Tconv cells nor in TGF-b-induced Treg [17,18]. Second, the groups of Fazekas de Saint Groth and Bluestone reported that human CD4 1 CD25 1 Treg can be distinguished from activated (and thus also CD25 1 ) Tconv cells by their different surface expression levels of CD127 (IL-7 receptor a-chain, IL-7Ra): whereas activated Tconv cells are strongly positive for CD127, Treg show only low or no expression of this marker [19,20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation